Pengaruh Utang Jangka Pendek, Utang Jangka Panjang, dan Asset Turnover terhadap Profitabilitas - Rhaisha Greshiana; M Hendri Yan Nyale (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of short-term debt, long-term debt, and asset turnover on profitability, using control variables such as liquidity, firm age, firm size, and tangible assets. The objects of this research are companies in the Restaurant, Hotel & Tourism sub-sector and the Retail Trade sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The data used is secondary data in the form of audited financial statements. This study employs purposive sampling as the sample selection method, resulting in a total of 45 sample data, and applies a quantitative method with panel data regression analysis. The results of this study show that short-term debt and long-term debt have an insignificant effect on profitability, whereas asset turnover has a significant and positive effect on profitability.